Clostridial Infection After Open Fractures of the Lower Extremity – Report of Two Cases and Discussion of Pathomechanism and Treatment - TREMP, MATHIAS (In Vivo, 2020)
Background: Management of post-traumatic open fractures resulting from severe injuries of the lower extremity continues to challenge orthopedic and reconstructive surgeons. Moreover, post-traumatic osteoarticular infections due to Clostridium species are rare, with few reports in the literature. We describe possible pathomechanisms and propose treatment options for cases of delayed diagnosis of osteoarticular infections with Clostridium spp. Case Reports: Two patients sustained severe osteoarticular infection due to Clostridium spp. after open epi- and metaphyseal fractures of the lower extremity. In combination with radical debridement, ankle arthrodesis and long-term antibiotic treatment, satisfactory results were achieved after a follow-up of 18 months and 24 years. Conclusion: Clostridium species are difficult to identify, treatment is usually delayed and most patients have unfavourable outcomes.